The (Perceived) Vanishing of the Leisure Class: Views from Weber, Veblen, and Piketty - Berardi, Gayle Kathleen; Segady, Thomas (Advances in Social Sciences Research Journal, 2016)
The French economist Thomas Piketty has recently provided extensive documentation that economic inequality in the most developed countries has grown and will continue to grow. Relying on data primarily from Britain, France--and to a lesser extent, the United States and Germany-- Piketty asserts that this trend will continue, barring events such as major wars or internal revolutions. Weber saw capitalism in much the same terms, emphasizing slow capital accumulation over relatively long periods of time, which brought distinction and legitimacy to the holder of large amounts of capital. Veblen focused on the conspicuous display of this legitimation. However, in light of the extent of global capital Piketty’s analysis provides clues to reasons for the emergence of global flows of capital combined with the perceived physical disappearance of wealthy capitalists themselves.